Porcine anti-human lymphocyte immunoglobulin depletes the lymphocyte population to promote successful kidney transplantation - Zhang, Limin; Zou, Haoyong; Lu, Xia; Shi, Huibo; Xu, Tao; Gu, Shiqi; Yu, Qinyu; Yin, Wenqu; Chen, Shi; Zhang, Zhi; Gong, Nianqiao (Frontiers in Immunology, 2023)
Porcine anti-human lymphocyte immunoglobulin (pALG) has been used in kidney transplantation, but its impacts on the lymphocyte cell pool remain unclear. We retrospectively analyzed 12 kidney transplant recipients receiving pALG, and additional recipients receiving rabbit anti-human thymocyte immunoglobulin (rATG), basiliximab, or no induction therapy as a comparison group. pALG showed high binding affinity to peripheral blood mononuclear cells (PBMCs) after administration, immediately depleting blood lymphocytes; an effect that was weaker than rATG but stronger than basiliximab. Single-cell sequencing analysis showed that pALG mainly influenced T cells and innate immune cells (macrophages and neutrophils). By analyzing immune cell subsets, we found that pALG moderately depleted CD4+T cells, CD8+T cells, regulatory T cells and NKT cells and mildly inhibited antigen presenting cells. Serum inflammatory cytokines (IL-2, IL-6) were only moderately increased compared with rATG, which might be beneficial in terms of reducing the risk of untoward immune activation. During 3 months of follow-up, we found that all recipients and transplanted kidneys survived and showed good organ function recovery; there were no cases of rejection and a low rate of complications. In conclusion, pALG acts mainly by moderately depleting T cells and is thus a good candidate for induction therapy for kidney transplant recipients. The immunological features of pALG should be exploited for the development of individually-optimized induction therapies based on the needs of the transplant and the immune status of the patient.